Immediate Outcome of Percutaneous Balloon Mitral Valvotomy in Shahid Gangalal National Heart Centre, Bansbari, Kathmandu, Nepal - Shrestha, Nagma; Bhatta, Yadav Kumar Dev; Maskey, Arun; Malla, Rabi; Rajbhandari, Rajib; Kansakar, Subodh; Sharma, Ranjit; Yadav, Dharmanath; Adhikari, Chandra Mani; Prajapati, Dipanker; et al. (Nepalese Heart Journal, 2015)
Background and Aim: Percutaneous balloon mitral valvotomy is well established as safe and effective procedure for patients with mitral stenosis due to Rheumatic Heart Disease. There are some retrospective studies on safety and efficacy of it in different subgroups of patients from our centre. Our study aims to assess the safety, efficacy and outcome of it in Shahid Gangalal National Heart Centre, Kathmandu, Nepal. Methods: A Single centre, prospective study was conducted from July 1st 2013 to June 31st 2014 in our centre. All the patients who underwent percutaneous balloon mitral valvotomy for moderate to severe mitral stenosis during the study period were included. Safety and efficacy of the procedure was analyzed. Results: There were 262 patients enrolled in the study among which 194 (74%) were females. Mean age of patients was 33.2±12.5 years. Seventy patients (26.7%) were in atrial fibrillation, six (2%) were pregnant, three (1%) had history of stroke, twelve (4.6%) underwent previous surgical or balloon commissurotomy. The mean left atrial pressure reduced from 26.8 ± 8.9 mmHg to 15.6 ± 7.2 mmHg (p < 0.05).The mean mitral valve area increased from 0.9 ± 0.17 cm2 to 1.6 ± 0.28 cm2 (p < 0.05). Forty nine patients (18.7%) developed moderate to severe mitral regurgitation. There was no mortality related to the procedure. The procedural success was achieved in 84% patients. Conclusion: Our study suggests that percutaneous balloon mitral valvotomy is a safe and effective procedure for symptomatic mitral stenosis patients. DOI: http://dx.doi.org/10.3126/njh.v12i1.12325 Nepalese Heart Journal Vol.12(1) 2015: 11-14